Impact and Lessons From the Lifestyle Interventions and Independence for Elders (LIFE) Clinical Trials of Physical Activity to Prevent Mobility Disability. Issue 4 (27th February 2020) - Pahor, Marco; Guralnik, Jack M.; Anton, Stephen D.; Ambrosius, Walter T.; Blair, Steven N.; Church, Timothy S.; Espeland, Mark A.; Fielding, Roger A.; Gill, Thomas M.; Glynn, Nancy W.; Groessl, Erik J.; King, Abby C.; et al.
Abstract : BACKGROUND: Walking independently is basic to human functioning. The Lifestyle Interventions and Independence for Elders (LIFE) studies were developed to assess whether initiating physical activity could prevent major mobility disability (MMD) in sedentary older adults. METHODS: We review the development and selected findings of the LIFE studies from 2000 through 2019, including the planning phase, the LIFE‐Pilot Study, and the LIFE Study. RESULTS: The planning phase and the LIFE‐Pilot provided key information for the successful implementation of the LIFE Study. The LIFE Study, involving 1635 participants randomized at eight sites throughout the United States, showed that compared with health education, the physical activity program reduced the risk of the primary outcome of MMD (inability to walk 400 m: hazard ratio = 0.82; 95% confidence interval = 0.69‐0.98; P = .03), and that the intervention was cost‐effective. There were no significant effects on cognitive outcomes, cardiovascular events, or serious fall injuries. In addition, the LIFE studies provided relevant findings on a broad range of other outcomes, including health, frailty, behavioral outcomes, biomarkers, and imaging. To date, the LIFE studies have generated a legacy of 109 peer‐reviewed publications, 19 ancillary studies, and 38 independently funded grants and clinical trials, and advanced the development of 59 early career scientists. Data and biological samples of the LIFE Study are now publicly available from a repository sponsored by the National Institute on Aging (https://agingresearchbiobank.nia.nih.gov ). CONCLUSIONS: The LIFE studies generated a wealth of important scientific findings and accelerated research in geriatrics and gerontology, benefiting the research community, trainees, clinicians, policy makers, and the general public. J Am Geriatr Soc 68:872–881, 2020 Abstract: See related editorial by LaCroix et al . in this issue.